THE EFFECTIVENESS OF USING CLUSTER CONNECTION TOWARDS STUDENTS’ VOCABULARY MASTERY AT THE EIGHTH GRADE OF MTs DARUL IHSAN DURI - setiawati, setiawati (AL-ISHLAH: Jurnal Pendidikan, 2017)
Penelitian ini bertujuan mengetahui keefektifan penggunaan cluster connection terhadap penguasaan kosakata siswa pada siswa kelas 8 MTs Darul Ihsan Duri. Behubungan dengan objek penelitian, peneliti menggunakan metode eksperimen. Model penelitiannya adalah kelompok pretest--post test untuk kelas control dan eksperimen. Penelitian ini diadakan pada MTs Darul Ihsan Duri pada tahun akademik 2015/2016. Populasi penelitian ini adalah kelas 8 MTs Darul Ihsan Duri pada tahun akademik 2015/2016. Total populasi penelitian adalah 62 siswa. Sampel penelitian ini adalah kelas VIII.A sebagai kelas kontrol, dan VIII.B sebagai kelas eksperimen. Kelas VIII.A terdiri atas 31 siswa. Kelas VIII.B terdiri atas 31 siswa. Dalam menganalisis data peneliti menggunakan Independent Sample T-Test. T-Test digunakan untuk mengetahui apakah teknik cluster connection effektif terhadap penguasaaan kosakata siswa. Hasil penelitian menunjukan bahwa penggunaan teknik cluster connection efektif terhadap penguasaaan kosakata siswa. Berdasarkan perhitungan statistic dalam menganalisis data peneliti memberikan tafsiran skor postest pada kelas eksperimen dan kelas kontrol. Dari perhitungan, t-test adalah 2.627 dan t-table adalah 2.00. karena nilai t-test (2.627) lebih tinggi dari pada t-table (2.00). Berdasarkan hasil penelitian, dapat disimpulkan bahwa alternative hipotesis (Ha) diterima dan hipotesis null (Ho) ditolak. Ini berarti pengajaran kosakata dengan teknik cluster connection adalah efektif. This study aimed to know The Effectiveness of Using Cluster Connection Towards The Students’ VocabularyMastery at The Eighth Graders at MTs Darul Ihsan Duri. Related to the object of the research, the researcher used experimental method. The design of the research was control and experiment group; pretest – posttest design. The research was conducted at MTs. Daru lIhsan Duri in the academic year 2015/2016. The population of this research was the eighth grade students of MTs Darul Ihsan Duri. The total population was 62 students. The sample of the research was class VIII.A as control class and class VIII.B as experimental class. Class VIII.A consisted of 31 students. Class VIII.B consisted of 31 students. In analyzing the research data, the researcher used Independent sampleT-Test. T-Test was used to know whether cluster connection technique is effective toward the students’ vocabulary mastery. The result of the research showed that using cluster connection technique was effective toward the students’ vocabulary mastery. Based on statistical calculation in data analysis, the researcher gave interpretation of posttest score in experiment class and the control class. From the calculation, t-test value was 2.627 and t-table was 2.00. Because t-test value (2.627) was higher than t-table (2.00), it could be concluded that alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It means that teaching vocabulary by using cluster connection is effective.